Guilt and Atonement? Communal Disasters and the Creation of Hero-Cults in Ancient Greece - Unfricht, Armin (Sapiens ubique civis, 2020)
In Greek Antiquity, communal suffering and misfortune was often interpreted as resulting from divine or supernatural ill-will. In some accounts, it is a wrathful heros who is the cause, and a cult has to be instituted in order to appease him and possibly gain a powerful ally. In this article, I focus on narratives where the hero receiving a cult in this fashion is a historical figure. Specifically, I analyze the different elements of these narratives in regards to how they characterize and frame the hero and his relationship towards his community, focusing especially on the function of the collective disasters and afflictions in these tales.